A novel citrate synthase isoform contributes infection and stress resistance of the stripe rust fungus. (30th October 2018) - Li, Dan; Pang, Lijing; Yuan, Pu; Zheng, Peijing; Huai, Baoyu; Yao, Mohan; Kang, Zhensheng; Liu, Jie
Summary: The early development of a rust fungus is dependent on the endogenous lipids stored in the urediniospores. After it establishes a parasitic relationship with the host, sugars absorbed from the host cells by haustoria become the primary nutrients. The tricarboxylic acid (TCA) cycle is essential to oxidize these nutrients. However, few studies have addressed the role of citrate synthase (CS), a rate‐limiting enzyme of the TCA cycle, during the infection process of rust fungi. In this study, a CS gene from Puccinia striiformis f. sp. tritici ( Pst ), PsCS1, was cloned and characterized. Transcripts of PsCS1 and the enzyme activity of the CS were increased in the early Pst infection stage. Biochemical features and subcellular localization revealed that PsCS1 encoded a mitochondrial CS. Size exclusion chromatography, yeast two‐hybrid and bimolecular fluorescence complementation experiments confirmed that PsCS1 could form a functional homo‐octamer. The overexpression of PsCS1 enhanced the resistance of Escherichia coli to salt stress. The knockdown of PsCS1 using a host‐induced gene silencing (HIGS) system blocked Pst growth in wheat. These results indicate that PsCS1 is required for nutrient metabolism in Pst and contributes to Pst infection by regulating ATP production and the supply of carbon sources.